Teacher Recruitment and Selection Process as a Strategy for Strengthening Human Resources at Ash Shiddiiqi Integrated Islamic School - Siti Roisah (Journal of Educational Sciences, 2026)
The quality of human resources (HR) of teachers is the main factor that determines the quality of education in a school. Teacher recruitment and selection is a strategic process to ensure that schools get competent educators, qualified both academically and character, and aligned with the institution's vision. This study aims to describe the teacher recruitment and selection process at the Ash Shiddiiqi Integrated Islamic School in Jambi City as a strategy for strengthening human resources. The research method uses a qualitative approach and case study method, data were collected through in-depth interviews, and documentation. The results show that a systematic teacher recruitment and selection process, consisting of planning and analyzing teacher needs, vacancy announcements through social media, administrative screening, academic tests, microteaching, Al-Qur'an tests, competency and moral or attitude interviews, and orientation or internship periods, can improve the quality of human resources (HR) and reduce the turnover rate or teacher turnover. Thus, structured teacher recruitment and selection plays an important role in strengthening human resources at the Ash Shiddiiqi Integrated Islamic School in Jambi City.